2013
DOI: 10.1186/1741-7015-11-68
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mechanisms of excess mortality with early fluid resuscitation: insightsfrom the FEAST trial

Abstract: BackgroundEarly rapid fluid resuscitation (boluses) in African children with severe febrile illnesses increases the 48-hour mortality by 3.3% compared with controls (no bolus). We explored the effect of boluses on 48-hour all-cause mortality by clinical presentation at enrolment, hemodynamic changes over the first hour, and on different modes of death, according to terminal clinical events. We hypothesize that boluses may cause excess deaths from neurological or respiratory events relating to fluid overload.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
173
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(191 citation statements)
references
References 33 publications
9
173
3
3
Order By: Relevance
“…This was reflected in a statistically significant difference in between the groups in the repeated measures linear regression analysis and differences between groups at both 9 and 12 hours post resuscitation. This result has some parallels to the exploratory analysis of increased mortality seen in the landmark FEAST trial 26 . In the post hoc analysis of the excess mortality the authors noted that the largest contributor to the excess mortality seen with fluid resuscitation was delayed cardiovascular collapse occurring between 2-11 hours.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This was reflected in a statistically significant difference in between the groups in the repeated measures linear regression analysis and differences between groups at both 9 and 12 hours post resuscitation. This result has some parallels to the exploratory analysis of increased mortality seen in the landmark FEAST trial 26 . In the post hoc analysis of the excess mortality the authors noted that the largest contributor to the excess mortality seen with fluid resuscitation was delayed cardiovascular collapse occurring between 2-11 hours.…”
Section: Discussionmentioning
confidence: 56%
“…In a secondary analysis of the FEAST trial authors demonstrated that the excess mortality in the FR arms was due to delayed cardiovascular collapse, a potentially novel mechanism of harm 12 . Consequently, we aimed to examine the effectiveness of FR in the treatment of septic shock in an animal model of endotoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…12 A reanalysis of this study suggested that cardiovascular collapse was linked to the increased mortality rather than respiratory failure due to pulmonary oedema. 13 Despite the lack of high-quality IV fluid trials in developed world populations, there is a signal of harm including complications noted in one in five patients in the NHS. 14 Consistent with this, observational studies performed in an intensive care setting have found associations between a positive fluid balance and increased mortality in inflammatory conditions and AKI.…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4)(51)(52)(53) The Fluid Expansion as Supportive Therapy (FEAST) study indicated that, while fl uid management is important in paediatric life support, it needs to be judiciously administered. (51,52) The recommended initial resuscitation fl uid of choice in infants and children remains as isotonic crystalloids. (54,55) If the patients show signs of inadequate systemic perfusion, they may benefi t from a bolus of 20 mL/kg of an isotonic crystalloid.…”
Section: Fluid Managementmentioning
confidence: 99%